2017
DOI: 10.1590/0074-02760160527
|View full text |Cite
|
Sign up to set email alerts
|

Minimal inhibitory concentration distributions and epidemiological cutoff values of five antifungal agents against Sporothrix brasiliensis

Abstract: BACKGROUNDSporothrix brasiliensis is the most virulent sporotrichosis agent. This species usually responds to antifungal drugs, but therapeutic failure can occur in some patients. Antifungal susceptibility tests have been performed on this species, but no clinical breakpoints (CBPs) are available. In this situation, minimal inhibitory concentration (MIC) distributions and epidemiological cutoff values (ECVs) support the detection of identification of resistant strains.OBJECTIVES To study the MIC distributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 29 publications
7
32
1
Order By: Relevance
“…Significant differences in antifungal susceptibilities have been observed among the four pathogenic species of the genus Sporothrix. In general, antifungal drugs show a good response against Sporothrix isolates from Brazil, especially terbinafine [23,[47][48][49][50]. In our reports, terbinafine was effective in vitro and in vivo, with remission of all clinical signs initially presented, as previously described in most cases of sporotrichosis in humans treated with this drug [21,22,[51][52][53][54].…”
Section: Discussionsupporting
confidence: 77%
“…Significant differences in antifungal susceptibilities have been observed among the four pathogenic species of the genus Sporothrix. In general, antifungal drugs show a good response against Sporothrix isolates from Brazil, especially terbinafine [23,[47][48][49][50]. In our reports, terbinafine was effective in vitro and in vivo, with remission of all clinical signs initially presented, as previously described in most cases of sporotrichosis in humans treated with this drug [21,22,[51][52][53][54].…”
Section: Discussionsupporting
confidence: 77%
“…ECVs should distinguish the two populations (WT and non-WT) that are present in the MIC/MEC distribution of a species and agent combination. ECVs for S. brasiliensis and some agents were recently reported using data from a single laboratory (28). However, the definition of ECVs using data from multiple laboratories allows the evaluation of modal (more frequent values in each MIC/MEC distribution) compatibility among the individual distributions included in the pool (a CLSI requirement) (24).…”
Section: Resultsmentioning
confidence: 99%
“…This heterogeneity could be related to the intra-species genetic variation and/or differences in gene expression. Almeida-Paes et al (2017) reported that S. brasiliensis isolates from human and cats with sporotrichosis had similar sensibility to azoles, but exhibited differences to amphotericin B and terbinafine susceptibilities ( Almeida-Paes et al, 2017 ). The lower sensitivity of feline-borne isolates to tacrolimus as monotherapy may stem from an adaptation of fungal isolates to the higher body temperature encountered in cats (compared with that found in humans).…”
Section: Discussionmentioning
confidence: 99%